2014
DOI: 10.1093/mnras/stu2195
|View full text |Cite
|
Sign up to set email alerts
|

Should we believe the results of ultraviolet–millimetre galaxy spectral energy distribution modelling?

Abstract: Galaxy spectral energy distribution (SED) modelling is a powerful tool, but constraining how well it is able to infer the true values for galaxy properties (e.g. the star formation rate, SFR) is difficult because independent determinations are often not available. However, galaxy simulations can provide a means of testing SED modelling techniques. Here, we present a numerical experiment in which we apply the SED modelling code MAGPHYS to ultraviolet (UV)-millimetre (mm) synthetic photometry generated from hydr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 174 publications
(246 reference statements)
0
96
0
Order By: Relevance
“…This may indicate a hidden, radio emitting AGN, but from our SED analysis in Section 4, we have shown that if HLock01-R harbors an AGN, its contribution to the total L IR and SFR is modest (;1%), as also noted by Rigopoulou et al (2018), and even assuming a maximum of 20% of an AGN contribution to the IRAC fluxes, the stellar mass of HLock01-R will be lower only by 0.1 dex, which is within our measurement errors. Moreover, Hayward & Smith (2015) have also shown that the physical properties derived using MAGPHYS are robust even when the AGN contributes 25% of the total UV to IR luminosity. Our deep GTC/OSIRIS rest-frame UV spectroscopy does not show any line or continuum emission at the positions of the lensed 13 images of HLock01-R, as some of them are included in the regions covered by our long-slit spectra (see Figure 1, left panel).…”
Section: Physical Propertiesmentioning
confidence: 95%
“…This may indicate a hidden, radio emitting AGN, but from our SED analysis in Section 4, we have shown that if HLock01-R harbors an AGN, its contribution to the total L IR and SFR is modest (;1%), as also noted by Rigopoulou et al (2018), and even assuming a maximum of 20% of an AGN contribution to the IRAC fluxes, the stellar mass of HLock01-R will be lower only by 0.1 dex, which is within our measurement errors. Moreover, Hayward & Smith (2015) have also shown that the physical properties derived using MAGPHYS are robust even when the AGN contributes 25% of the total UV to IR luminosity. Our deep GTC/OSIRIS rest-frame UV spectroscopy does not show any line or continuum emission at the positions of the lensed 13 images of HLock01-R, as some of them are included in the regions covered by our long-slit spectra (see Figure 1, left panel).…”
Section: Physical Propertiesmentioning
confidence: 95%
“…This code has been tested on simulated isolated galaxies and major mergers and has been shown to correctly retrieve   , SFRs, and L IR of the simulated objects (Hayward & Smith 2015). It was also shown in da Cunha et al (2013) that MAGPHYS, when used to fit U−K photometry, can accurately predict the L IR derived for the same galaxies from Herschel measurements.…”
Section: Sfrs Stellar Masses and Sizesmentioning
confidence: 96%
“…To date, there are still a few studies that explore and quantify the impact of AGN contamination on the determination of the underlying host galaxy properties via SED-fitting (Wuyts et al 2011;Hayward & Smith 2015). In this paper, we address this using the Bayesian-based SED-fitting code CIGALE (Noll et al 2009, Burgarella et al, in prep.…”
Section: Introductionmentioning
confidence: 99%